PENGARUH WEBSITE QUALITY TERHADAP MINAT BELI PRODUK START UP BUSINESS MAHASISWA - Deandra Vidyanata (SEGMEN Jurnal Manajemen dan Bisnis, 2021)
During the past decade, people around the world has experienced a rapid change in relation with technology, such as a website. The purpose of this research is to find out the impact of website quality towards purchase intention. In this research website quality is examined using the WebQual dimension, therefore the variables used are usefulness, ease of use, entertainment, and complementary relationships. The data collection process needed in this research using a purposive sampling method with sample criteria of individuals who have bought and visited start up business’ website. This research uses a sample of 85 respondents. The analytical method used in this research is quantitative method with multiple linear regression analysis to find out the influence of the variables of usefulness, ease of use, entertainment and complementary relationships on purchase intention. It is found that the usefulness positively significant towards purchase intention as well as the entertainment and complementary relationship that have a positive influence on purchase intention. While the ease of use is known not to have a significant influence towards purchase intention